A comparison of two intravesical bladder instillations for interstitial cystitis/bladder pain syndrome. (January 2021) - Keane, J.; Young, N.; Goh, J.; Atherton, M.; Yin, J.; Moore, K.; Hall, P.; Higgs, P.; Leitch, A.; Lee, J.; Rosamilia, A.
Abstract: Objective: Bladder pain syndrome (BPS) is a chronic pain condition associated with injury to the glycosoaminoglycan (GAG) layer. We aimed to prospectively evaluate iAluRil® with multi-centre tertiary urogynaecology collaboration. We hypothesised that iAluRil® (a GAG therapy) would demonstrate equivalent symptom, pain and QOL scores compared to DMSO controls. Study Design: iAluRil® was administered for 7 instillations over 3 months in 34 women over 6 sites. 18 historical DMSO controls were matched 2:1. At baseline and 3 months post treatment validated questionnaires were collected. Results: Both iAluRil® and DMSO were associated with statistically significant improvements in IC/BPS specific questionnaire scores. iAluRil® showed statistically significant improvements in pain, symptoms, and QOL. 45 % of iAluRil® recipients had a greater than 50 % reduction in pain score as represented by the VAS. DMSO was also effective in improving measures of IC/BPS with statistically significant decreases in ICSI and ICPI. There was no statistically significant difference in the size of the effect between DMSO and IAluRil®. Conclusions: iAluRil® is well tolerated and associated with significant improvements in pain and symptom scores. Almost half of refractory BPS will have a 50 % decrease in pain score at three months post treatment. This effect size is similar to DMSO.